ANALYSIS OF METACOGNITIVE CHARACTERISTICS OF DECISION-MAKING IN MANAGERS’ NEGOTIATION ACTIVITIES. - Toshov Muhiddin Jurabayevich (Research Focus International Scientific Journal, 2024)
This article explores the historical development of social pedagogy across various international contexts, tracing its evolution from the 19th century to the present. Social pedagogy, broadly defined as the intersection of social work and education, emphasizes a holistic approach to personal and societal well-being. The study investigates how different countries have shaped social pedagogy through unique educational and social welfare perspectives, influenced by cultural, political, and economic factors. By examining key contributions from countries such as Germany, Denmark, the United Kingdom, and Brazil, this paper highlights the diverse approaches to social pedagogy and discusses its role in contemporary society. The findings underscore the importance of social pedagogy in fostering social inclusion, addressing inequality, and promoting community-based solutions in education.